Photooligomerization determines photosensitivity and photoreactivity of plant cryptochromes - Liu, Qing (Mol Plant, 2020)
Plant and non-plant species possess cryptochrome (CRY) photoreceptors to mediate blue-light regulation of development or the circadian clock. The blue light-dependent homooligomerization of Arabidopsis CRY2 is a known early photoreaction necessary for its functions, but the photobiochemistry and function of light-dependent homooligomerization and heterooligomerization of cryptochromes, collectively referred to as CRY photooligomerization, have not been well-established. Here we show that photooligomerization is an evolutionarily conserved photoreaction characteristic of the CRY photoreceptors in plant and some non-plant species. Our analyses of the kinetics of the forward and reverse reactions of photooligomerization of Arabidopsis CRY1 and CRY2 provide a previously unrecognized mechanism underlying the different photosensitivity and photoreactivity of these two closely related photoreceptors. We found that photooligomerization is necessary but not sufficient for the functions of CRY2, implying that CRY photooligomerization must accompany with additional function-empowering conformational changes. We further demonstrate that the CRY2-CRY1 heterooligomerization plays roles in regulating functions of Arabidopsis CRYs in vivo. These results are consistent with the hypothesis that photooligomerization is an evolutionary conserved mechanism that determines the photosensitivity and photoreactivity of plant CRYs.